2012
DOI: 10.1186/1471-2458-12-554
|View full text |Cite
|
Sign up to set email alerts
|

Different Points of a Continuum? Cross Sectional Comparison of the Current and Pre-contact Psychosocial Problems among the Different Categories of Adolescents in Institutional Care in Nigeria

Abstract: BackgroundThe combination of adverse social indicators and a predominantly youthful population puts Nigeria, and indeed many countries of sub-Sahara Africa, at the risk of explosion in the number of youth coming in contact with the juvenile justice system. Despite this risk, custodial childcare systems in the region are still poorly developed with both juvenile offenders and neglected adolescents coming in contact with the systems being kept in the same incarcerating facility. The needs of these different grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 45 publications
2
28
0
2
Order By: Relevance
“…[10][11][12][13] The relevance of environmental factors has also been proposed by many authors who studied children and adolescents with antisocial behaviors. [14][15][16] Curto et al, for example, found that severe physical punishment and having an absent father/substitute at home were significantly associated with adolescent antisocial behavior in a low-income community in Brazil. 17 In spite of these findings, it still unclear which aspects of personality --constitutional or psychosocial --differentiate young offenders from non-offenders with a similar socioeconomic background.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The relevance of environmental factors has also been proposed by many authors who studied children and adolescents with antisocial behaviors. [14][15][16] Curto et al, for example, found that severe physical punishment and having an absent father/substitute at home were significantly associated with adolescent antisocial behavior in a low-income community in Brazil. 17 In spite of these findings, it still unclear which aspects of personality --constitutional or psychosocial --differentiate young offenders from non-offenders with a similar socioeconomic background.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale studies from the developed countries have found a higher prevalence of mental health problems among children in single-parent families [40]. Similar large-scale studies are yet to be conducted in subSaharan Africa but small-scale studies have established links between family-life deficits and adverse social and mental health outcomes for children [41,42].…”
Section: Poorly Resourced Families As a Risk And Vulnerabilitymentioning
confidence: 99%
“…Unfortunately, despite a high need for juvenile justice and child social-welfare services in many parts of subSaharan Africa, these systems are still poorly developed in the region [42,94,95]. The care of children in contact with social welfare and juvenile justice institution in the region is still hinged largely on punitive incarceration or institutional seclusion without much framework for true reformation or addressing their social and mental health needs [42,96].…”
Section: Lack Of Adequate Community and Institutional Childcarementioning
confidence: 99%
“…For instance, a study among young 'offenders' in Abeokuta Borstal home revealed that being deemed 'beyond parental control' and/or being involved in non-violent theft constituted 90 per cent of the 'offences' committed by the child prisoners (Atilola, 2012a). Ajiboye et al (2009) borstal home in Ilorin.…”
Section: Penal Severitymentioning
confidence: 99%